Sustainable Improvement of Profit Strategy Through Synergy Profit Sharing with Investor, Case Study: The Establishment of Cassiavera Factory from CV Kerinci Agro - Putra, Hengki Anggo; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2013)
The world demand for spices and herbs has soared for use food preservation, food flavoring, aromatherapy, beverages, personal hygiene product, industrial chemicals, pharmaceutical, and feeds. According Food and Organization of The United State, Indonesia as the world leader of the cinnamon with produces 63.4 thousand metric tons of cinnamon average between 1999 to 2001 the contrary the small holders and the farmers in cinnamon plantation are difficult to get bargaining position and receive more profit. This problem can be solve by maximize the value of cinnamon with modernization of cinnamon processing, the author uses three combine method analyses the case: first feasibility study analysis with variable such as IRR, NPV, ROI and Payback Period to determine project. The second is strategic business to determine the best corporate strategy, and the last analysis is risk analysis to determine the risk of the business. The business solution show that feasibility study analysis result IRR of 72.60%, NPV IDR 12,271,128,366, ROI 262.61% and Payback Period 1.57 years. The second analysis is business strategy show that CV Kerinci Agro strategy is cost leadership and become reference to determine the new business strategy. The risk analysis shows that delayed project, fluctuation prices and bad reputation are the main issue risks to run the project. The end result of the final project show the project accepted with marketing, production, and finance aspect. Strategy business require from cost leadership to differential. Analysis risk shows that delayed project, fluctuation prices and bad reputation are main issue risk. The farmer cinnamon will receive 4%-8% in synergy swap share. The author has recommended implementation plan: 1) Training Program.2) Organic Certification. 3) Mitigation risks: Hedging option, standard operational.Â Keyword: Feasibility Study, Business Strategy, and Analysis Risk